Inovasi Pembelajaran Pendidikan Agama Islam untuk Generasi Milenial - Ballianie, Novia; Dewi, Mutia; Fatimah, Siti (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze innovations in Islamic Religious Education (PAI) learning for the millennial generation. The research employs a literature review method, where data is gathered from various sources such as books, journal articles, research reports, dissertations, and other relevant written documents, without conducting direct experiments or surveys. The data analysis technique in this study involves stages of data collection, classification and organization, content analysis, information synthesis, and conclusion drawing. Based on the findings, digital-based innovations in PAI learning utilize technology to enhance the effectiveness, interactivity, and relevance of the learning process for students in the digital era. With integrated technology, PAI learning becomes more engaging and easier to understand, particularly for a generation accustomed to technology. The use of interactive multimedia also makes PAI learning more meaningful and tailored to the needs of the millennial generation. Additionally, an open and collaborative discussion approach in PAI not only supports students' understanding of religious material but also helps shape character aligned with Islamic values. This approach makes PAI learning more interactive and closely related to students' lives, strengthening the connection between religious concepts and daily practices.